(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The overall health and productivity of an economy has a considerable impact on a well-developed and functioning capital market. Finally, the capital market development and overall economic activity go hand in hand. As a result of the securities listing on a foreign stock exchange, companies formed in India that want to issue shares on overseas markets will be able to raise money at a cheaper cost. This new framework will enhance the growth and development of the Indian economy. Additionally, the listing of companies outside of India on Indian stock exchanges will help increase the allocation of money and help investors diversify their investment options. As an exercise to accommodate global businesses, the SEBI decided that firms incorporated in India should be allowed to list their equity securities on foreign exchanges, while outside incorporated companies should be allowed to list their shares on Indian Secondary market platform. This study is intended to find out whether proposed norms are successful, and if they are, to discover how they work. The study is much more in-depth on this topic, in which it addresses both international and Indian firms going public on Indian stock exchanges directly.